Lake-Level fluctuations at Le Locle, Swiss Jura, from the Younger Dryas to the Mid-Holocene: A high-resolution record of climate oscillations during the final deglaciation - Magny, Michel; Schoellammer, Patrick (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1999)
Abstract On the basis of a high-resolution (10 cm / 110 years) lacustrine sequence from Le Locle, Swiss Jura, a fine-scale pattern of palaeohydrological changes is reconstructed for the late Younger Dryas (YD) and the early to mid-Holocene period. The late YD is characterized by a general trend of a fall in lake level and a large climatic instability. The early to mid-Holocene period shows a quasi-cyclic pattern of lake-level fluctuations. Large drops in lake level occurred at ca. 11 600-10 200 cal. BP and ca. 8 900-7 700 cal. BP. Each was interrupted by a short-term rise in lake-level and followed by a longer phase of high lake level respectively at ca. 10 200-8 900 cal. BP and ca. 7 700-6 600 cal. BP. The high lake-level periods at le Locle appear to be in phase with cold spells reconstructed in central Europe, in eastern North America and in the Greenland ice-sheet, or with cooling events and salinity anomalies recorded in the North Atlantic zone. They also coincide with rising residual Δ14C values. These data and the Lateglacial oxygen-isotope GISP2 record suggest three successive quasi-cycles of climatic and environmental changes showing strong similarities in their internal structure. These cycles suggest that large-scale climate oscillations developing from the Bølling warming to the mid-Holocene could have been associated with changes in ocean ventilation probably induced by three deglaciation steps. Finally, as a working hypothesis, a re-exami- nation of the YD event is proposed from a Holocene point of view.